EUROPEANIZATION AND DE‐EUROPEANIZATION IN UK EMPLOYMENT POLICY: CHANGING GOVERNMENTS AND SHIFTING AGENDAS. (10th October 2016) - COPELAND, PAUL
Abstract : This article analyses the UK's engagement with, and the subsequent impact of, the European Employment Strategy (EES). In doing so, it provides an example of the process of Europeanization under the Open Method of Coordination (OMC) in a Eurosceptic centralized polity. Under New Labour (1997–2010) the UK actively engaged to upload its preferences to the European political arena. At the national level, the UK experienced a process of Europeanization that was most evident in the cognitive and procedural dimensions. By contrast, during the coalition government the UK strategically withdrew from the EU governance process and reversed the procedural and cognitive shifts that had occurred under its predecessor. During the coalition government the UK therefore experienced a process of de‐Europeanization. The findings of the article highlight the limitations of OMC‐inspired Europeanization in a setting such as the UK.